Federal university hospitals: heterogeneity in the coordination of clinical trials authorized by the National Health Surveillance Agency - da Cunha, Claudia Simone Costa; Bittar, Olimpio Jose Nogueira Viana; Tess, Beatriz Helena (Clinical and Biomedical Research, 2021)
Introduction: This study aimed to describe clinical trials approved by the Brazilian Health Surveillance Agency (ANVISA) and coordinated by federal university hospitals (FUHs), as well as to investigate the relationship between the number of clinical trials and the assistance provided by these FUHs. Methods: This is a cross-sectional study based on data obtained from the ANVISA clinical trial consultation system. The National Register of Health Care Facilities and the Ambulatory Care Information System of the Unified Health System (SUS) were used as sources of information on the assistance provided by FUHs, such as the mean number of specialized medical consultations and the number of beds. Scatter plot and Spearman’s correlation coefficient analyses were used to verify the association between these aspects of FUHs and the number of clinical trials. Results: Between 2012 and 2013, ANVISA authorized 209 trials to be coordinated by 23 FUHs; 75% of the trials were coordinated by 7 FUHs, 69.8% were phase III trials, and 94% were multicenter studies. The number of clinical trials presented positive and statistically significant associations with the mean number of specialized medical consultations and the number of beds (Spearman’s correlation coefficients r = +0.70 and r = +0.64, respectively). Conclusion: FUHs have a leadership role in the conduction of clinical trials in Brazil, but showed heterogeneity regarding their assistance capacities and the number of clinical trials. A predominance of phase III trials may be interpreted as a low use of the scientific potentiality of these facilities.